PERTANGGUNGJAWABAN PELAKU PENYEBARLUASAN VIDEO PRIBADI YANG MENGANDUNG PRONOGRAFI MELALUI MEDIA SOSIAL TWITTER - Fahririn; Yuherman; Romandanti, Nika Wela (Esensi Hukum, 2023)
Many videos containing pornographic content are spread on social media, especially Twitter. Accounts containing immoral content are still active today and are still distributing pornographic photos and videos and there is no accountability received by the creators of these accounts, so the victims' videos are still being spread and becoming public consumption. This research uses a qualitative method with a literature study approach which will provide an explanation of the regulations related to the distribution of pornographic content and the sanctions that can be applied to perpetrators. The results of the research show that the principle of lex specialis derogate lex generalis in Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions creates criminal liability that can ensnare perpetrators of pornography crimes more specifically.